Regional Nodal Irradiation After Breast Conserving Surgery for Early HER2-Positive Breast Cancer: Results of a Subanalysis From the ALTTO Trial. (9th March 2017) - Gingras, Isabelle; Holmes, Eileen; De Azambuja, Evandro; Nguyen, David H. A.; Izquierdo, Miguel; Anne Zujewski, Jo; Inbar, Moshe; Naume, Bjorn; Tomasello, Gianluca; Gralow, Julie R.; Wolff, Antonio C.; Harris, Lyndsay; et al.
Abstract: Background: Two randomized trials recently demonstrated that regional nodal irradiation (RNI) could reduce the risk of recurrence in early breast cancer; however, these trials were conducted in the pretrastuzumab era. Whether these results are applicable to human epidermal growth factor receptor 2 (HER2)–positive breast cancer patients treated with anti-HER2-targeted therapy is unknown. Methods: This retrospective analysis was performed on patients with node-positive breast cancer who were enrolled in the Adjuvant Lapatinib and/or Trastuzumab Treatment Optimization phase III adjuvant trial and subjected to BCS. The primary objective of the present study was to examine the effect of RNI on disease-free survival (DFS). A multivariable cox regression analysis adjusted for number of positive lymph nodes, tumor size, grade, age, hormone receptors status, presence of macrometastatis, treatment arm, and chemotherapy timing was carried out to investigate the relationship between RNI and DFS. Results: One thousand six hundred sixty-four HER2-positive breast cancer patients were included, of whom 878 (52.8%) had received RNI to the axillary, supraclavicular, and/or internal mammary lymph nodes. Patients in the RNI group had higher nodal burden and more frequently had tumors larger than 2 cm. At a median follow-up of 4.5 years, DFS was 84.3% in the RNI group and 88.3% in the non-RNI group. No differences in regional recurrence (0.9 % vs 0.6 %) or in overall survival (93.6% vs 95.3%) were observed between the two groups. After adjustment in multivariable analysis, there was no statistically significant association between RNI and DFS (hazard ratio = 0.96, 95% confidence interval = 0.71 to 1.29). Conclusions: Our analysis did not demonstrate a DFS benefit of RNI in HER2-positive, node-positive patients treated with adjuvant HER2-targeted therapy. The benefit of RNI in HER2-positive breast cancer needs further testing within randomized clinical trials.